Microinversor monofásico baseado na derivação da topologia flyback para sistema de geração fotovoltaica - Freire, Fábio José Lima (2015)
The study proposes the design and implementation of a single phase inverter of single stage obtained the derivation of four flybacks converters CC - CC operating in discontinuous mode and associated in parallel modules. This arrangement reduces the amount of magnetic and decreases current efforts in primary transformers and minimizes fluctuations i n photovoltaic module. Among the main properties of micro inverter flyback (MIF) this research, the primary keys work with SPWM switching at high frequency and lagged in one hundred and eighty degrees, while the secondary keys are controlled by PWM's compl ementary. To validate the research, we will develop a prototype that will effect the processing power connecting a photovoltaic panel with 200W power in resistive loads with senoidais characteristics. The proposed system is based on the configuration of th e integrated module drive (MIC), which, in turn, has lower losses in the semi - conductors and magnetic elements of the topology, when compared to complex centralized photovoltaic systems. Among the applications of micro inverter flyback are: supply of remote systems, power electronics devices, small water pumping stations, connections to the grid, among others. Despite the low power, micro inverter has electrical characteristics essential for the insertion in the energy matrix, such as: insulation betwe en the source and the load, types of voltages and currents waves in output with little distortion and frequency of the network. The results obtained in the laboratory show that the micro inverter flyback operating in open loop gets yields close to 90% bein g delivered to the load about 180W. Thus, the ease of construction, the use of fewer components and results collected experimentally enable the micro inverter flyback to perform the CC - CA conversion of photovoltaic systems of small powers connected in sing le - phase linear loads with senoidais characteristics or interconnected to the electric grid